Daya Tahan Bakteri Escherichia coli terhadap Zat Warna Natrium Deoksilat dengan Uji Konfirmasi - PERMATA SARI, DINA; Urip , Drs.; Jiwintarum , Yunan; Fihirudin , Dr. (Journal of Indonesia Laboratory Students (JILTS), 2024)
Background: One group of Enterobacteriaceae bacteria is Escherichia coli, . These bacteria can live in the human large intestine, also known as enteric bacteria. This bacteria can cause gastrointestinal infections such as diarrhea, stomach ache, vomiting and nausea. This bacteria is resistant to several chemicals, such as the dye, namely brilliant green. This dye functions to inhibit gram-negative bacteria. From the description above, it is necessary to carry out a confirmation test to find out whether Escherichia coli bacteria can survive the dye Sodium deoxycholate by carrying out a confirmation test.Research purposes: to find out the picture of resilience Escherichia coli against sodium deoxycholate dyesResearch Method: The research design used was experimental. The sampling technique in this research used the Purposive Sampling Technique. The samples used were Escherichia coli and Staphylococcus aureus. The Most Probable Number (MPN) method consists of 2 tests, namely presumption and confirmation test. The presumptive test is an initial test using a liquid medium containing lactose, then incubated for 48 hours, if gas bubbles form in the presumptive test, proceed to the confirmation test.Research result: The resistance of Escherichia coli to sodium deoxycholate media by carrying out confirmation tests showed that the Escherichia coli bacteria were resistant to NDLB (Natrium Deoxycholate Lactose Broth) media, because when tested with LBDS and LBSS no gas bubbles were formed. Conclusion: Research that has been carried out shows that Sodium Deoxycholate media does not inhibit the growth of Escherichia coli bacteria and can be used as a replacement for BGLB.